THE EFFECT OF SERVICE QUALITY ON CUSTOMER LOYALTY OF MANDIRI BANK SEMARANG - Siburian, Ind Tigana Prasetyo; Waluyo, Handoyo Djoko; Widayanto, Widayanto (Jurnal Ilmu Administrasi Bisnis, 2012)
High competition is increasing in the marketing sphere specifically in the context of banking products. It determines the increase marketing activity therefore it is able either to maintain or to increase banking customer. The acts is by feature in quality of service and increase in qualityof customer satisfication’s rate. There is fluctuation  in the amount of customer Bank Mandiri Semarang in Branch-Pandanaran from 2005-2010. The goals of this inquiry is to find out the influence of equality of service and customer satification on customer loyality. The amount of population is 7517 people as customer and the sample of this inquiry is taken in 100 people based on purposive sampling technic. The data be analysed quanitatively and qualitatively using validity test, reability test, cross tab, and simple linear regression analysis, multiple linear regression, correlation test, F-test, and also utility determination’s correlation with SPSS software. Statistic data calculation shows that equation of simple linier regression between quality of service toward loyality of customer is Y = 1.078 + 0.255X1. Equation of simple linier regression between quality of service towards loyality of customer is Y = 0.549 + 0.565X2.. Equity of simple linier regression between quality of service towards customer’s satisfication is Z = 3.656 + 0.420X. From each of the equity, it can be found out that there is positif determination/influence partially in between variables X  towards variables Y. As multiple linear regression showed Y = 0.259 + 0.161X + 0.224Z, therefore can be found out that both of variables X have positif determination  towards variable Y. Hypothesis test shows that variable quality of service and customer’s satisfication have positif determination towards variable customer’s loyality. This refer to tcalculation all of variables is bigger than ttabel that is 1,661. Variable of quality of service has tcalculation 11.944. Variable of satisfication’s customer has tcalculation 11.549. Whereas from F-test can be acquired Fcalculation 75.505. All variables be tested with signification rate 5 %. Therefore the hypothesis can be accepted. From this inquiry, conclusion can be gotten that quality of service and customer’s satisfication is good enough. In order to increase loyality of customer Bank Mandiri in Branch- Pandanaran, its necessary to maintain and increase rate of cleanness both either in waiting room or toilet, to increase security level waiting room, and also to give clarity of information to customers about security’s quarantee of fundary of customer in Bank Mandiri in Branch- Pandanaran.